Pendampingan Distance Learning Berbasis Teknologi di SMK Negeri 1 Demak - Zuliana, Eka; Ahsin, Muhammad Noor; Purbasari, Imaniar (Dedikasi Nusantara: Jurnal Pengabdian Masyarakat Pendidikan Dasar, 2025)
Technology-based distance learning assistance program is a community service program aimed at teachers of SMK Negeri 1 Demak. The need for technology-based learning is currently increasing. The purpose of this PKM activity is to provide knowledge, training and mentoring to teacher partners related to technology-based distance learning. The method used in this service is to provide interactive training and mentoring. Furthermore, in the training process there is a two-way interaction so as to provide opportunities for SMK N 1 Demak teachers as trainees to contribute their ideas, opinions, thoughts, and experiences. While the implementation of mentoring is carried out in several stages, namely: planning, implementation, follow-up, and evaluation. The result of this service activity is that teachers of SMK Negeri 1 Demak are able to simulate and practice technology-based distance learning.